TALKING TO THE MAILMAN. - Lucas, Rob (New Left Review)
The article presents an interview with American free software movement activist Richard Stallman on topics including the people who influenced him in programming, the origins of the free-software movement, and the culture at the Massachusetts Institute of Technology's artificial intelligence lab.